OP0009 Rising prevalence of functional disability in patients with rheumatoid arthritis over 20 years. (12th June 2018) - Myasoedova, E.; Davis, J.M.; Achenbach, S.J.; Matteson, E.L.; Crowson, C.S.
Abstract : Background: Despite the advances in treatment of rheumatoid arthritis (RA) over the recent decades many patients with RA do not achieve remission or full physical functioning. The trends in prevalence of functional disability (FD) in patients with RA are not fully understood. Objectives: To assess the prevalence of patient-reported FD in patients with RA compared to subjects without RA over the past two decades of calendar time, across different age categories and over the duration of RA disease. Methods: This retrospective population-based cohort study included Olmsted County, MN residents who met 1987 ACR criteria for RA from 1/5/1999 to 12/31/2013 and a cohort of subjects without RA matched by age and sex from the same underlying population. Each non-RA subject was assigned an index date matching RA incidence date of a corresponding RA patient. Activities of Daily Living (ADL) were recorded annually over the past 20 years at patients' routine medical care visits based on patient provided information about performing six ADL without assistance including feeding oneself, dressing, using the toilet, bathing, walking, housekeeping. FD was defined as having difficulty with ≥1 of the six ADLs. Analyses were performed using age- and sex-adjusted logistic regression models with random subject effects to account for multiple measures per patient. Results: Five hundred eighty-six patients with RA (mean age 55, 70% females) and 531 non-RA subjects (mean age 56, 70% females) have completed 7446 questionnaires (4, 301 RA and 3145 non-RA) from 1/5/1999 to 1/5/2018 on or following their RA incidence/index date. There has been a significant increase in the prevalence of FD among patients with RA compared to the non-RA cohort over the past two decades (p=0.003, figure 1). When analysing by age group, patients with RA compared to the non-RA subjects had at least a 15%>excess in the proportion of FD at any given age up to the 8–9th decade of life while the proportions were similar in both cohorts. When analysing FD over the duration of RA disease, its prevalence was significantly higher in the RA compared to non-RA subjects, starting at RA incidence/index date (26% in RA vs 11% in non-RA subjects, p<0.001), with persistent excess in prevalence over the entire follow-up time. When FD was defined as having difficulty with ≥ 2 of the six ADLs the trends were similar for calendar year, age categories and RA disease duration, although the proportion of patients affected with functional disability was smaller. Conclusions: Patients with RA have significantly higher prevalence of FD compared to their non-RA counterparts. The prevalence of FD in RA has increased in the recent decades with a persistent excess in the proportion of affected patients in the RA compared to the non-RA cohort across the age-range and over RA disease duration. This substantial and growing FD burden is despite the recent advances in controlling RA disease activity with modern antirheumatic therapies. More studies are needed to understand the underlying causes for these trends in FD and to improve outcomes in patients with RA. Disclosure of Interest: None declared